Metabolite-derived protein modifications modulating oncogenic signaling - Liu, Yawen; Vandekeere, Anke; Xu, Min; Fendt, Sarah-Maria; Altea-Manzano, Patricia (Frontiers in Oncology, 2022)
Malignant growth is defined by multiple aberrant cellular features, including metabolic rewiring, inactivation of tumor suppressors and the activation of oncogenes. Even though these features have been described as separate hallmarks, many studies have shown an extensive mutual regulatory relationship amongst them. On one hand, the change in expression or activity of tumor suppressors and oncogenes has extensive direct and indirect effects on cellular metabolism, activating metabolic pathways required for malignant growth. On the other hand, the tumor microenvironment and tumor intrinsic metabolic alterations result in changes in intracellular metabolite levels, which directly modulate the protein modification of oncogenes and tumor suppressors at both epigenetic and post-translational levels. In this mini-review, we summarize the crosstalk between tumor suppressors/oncogenes and metabolism-induced protein modifications at both levels and explore the impact of metabolic (micro)environments in shaping these.